HISTOPATHOLOGICAL ALTERATIONS IN TESTES ON. CHRONIC DERMAL EXPOSURE OF CYPERMETHRIN IN WISTAR RATS - VERMA, P K; RAO, M MUTHA; SRILATHA, CH; RAINA, R (The Indian Journal of Animal Reproduction, 2010)
The effect of chronic dermal exposure of cypermethrin on the testicular tissue in Wistar rats(n=18) was studied. Multiple small to large vacuolation and necrosis in the epithelial lining of seminiferoustubules, eosinophilic secretions in interstitium and presence of single or multiple giant cell in thelumen of tubules were seen. The changes were found to be exposure dependant. These observationssuggest that chronic dermal exposure of cypermethrin cause degenerative changes in seminiferoustubules of rat testes.
Keywords: Dermal exposure; Cypermethrin; Wistar- rats; Testes